European Ambitions of the National Judiciary - Jansen, Rosa H.M.; Koster, Dagmar A.C.; Zutphen, Reinier F.B. van (International Law - Book Archive pre-2000., 1997)
Some years ago, SSR (The Dutch Training and Study Centre for the Judiciary) started a programme to reinforce and deepen knowledge of Community law among the members of the judiciary. Inquiry had revealed a tendency to leave matters of Community law to specialists and interested parties only, even though European law is part of the national legal system and all judges and public prosecutors should therefore be aware of their position as European magistrates. With this work, SSR would like to promote an increase in knowledge of European law among the members of the judiciary and, in particular, to heighten their consciousness of the existence and meaning of regulations of European law which are of immediate importance to the national administration of justice. Community law is a matter for all European countries, and uniformity, and the legal protection it affords, requires an univocal interpretation and application of the regulations of Community law among all member states. The book investigates several themes relating to the actual application of European law by members of the judiciary in everyday practice, including the development of the role of members of the national judiciaries regarding the maintenance of Community law, European norms, the consequences of negligence in the application and implementation of Community law, and the future conception of judicial responsibilities.